ISLAMIC PHILOSOPHY IN THE MOTIFS OF SARAWAK MALAY KERINGKAM - Rahah, Hasan (https://www.riec.unimas.my/borneo-intex25, 2025)
Based on delicate observation of existing Keringkam collection, this research merges traditional Sarawakian craftsmanship with intricate floral and geometric patterns, resulting in a striking balance of heritage and modernity. The first design features a radiating star motif created by intersecting lines, symbolizing focus and unity. Another pattern showcases a grid of interlocking triangles and squares, forming a rhythmic and balanced composition that draws the eye across the fabric.The highlight of the collection is a pattern inspired by the iconic Dewan Undangan Negeri building in Kuching, with its elegant peak s and arches, reflecting the grandeur of this architectural landmark its organic circular motifs overlap and intertwine, creating a sense of fluidity and movement, while a minimalist design inspired by traditional architectural elements features elegant peak s and arches. Each piece in this collection is a testament to the seamless blend of tradition and contemporary style, offering a sophisticated and timeless addition to any wardrobe.